Rapidly Progressive Osteolysis and a Large Cystic Lesion that Destroyed the Inner Table of the Iliac Bone Following Cementless Total Hip Arthroplasty : A Case Report - Daishi HAMADA; Toshiharu MORI; Manabu TSUKAMOTO; Yoshiaki YAMANAKA; Soshi UCHIDA; Akinori SAKAI (Journal of UOEH, 2018)
[Abstract :] We report a case of rapidly progressive osteolysis and a very large cystic lesion that destroyed the inner table of the iliac bone following cementless total hip arthroplasty (THA) . A 59-year-old female patient developed left hip pain at 11 years after THA. Osteolysis surrounding the acetabular cup was pointed out. She was brought to our hospital by ambulance due to severe left hip pain at 12 years after THA. Computed tomography (CT) showed that a cystic lesion in the pelvic cavity had destroyed the inner table of the iliac bone. Magnetic resonance imaging (MRI) showed a high signal intensity area of the hemorrhagic cystic lesion in the iliac bone in both T1-weighted and T2-weighted images. She underwent a liner and femoral head exchange, and required bone grafting and revision of the cup. The cystic lesion was removed and block-like allograft bone grafts were stuffed into the bone defects. If osteolysis and cystic lesions occur at the same time, not only the bone area around the implant but also a distant area like the inner table of the iliac bone may be destroyed. Additional tests such as CT or MRI may be useful to detect the presence of distant or cystic lesions. Early diagnosis and treatment are important because severe complications may occur in cases where osteolysis and cystic lesions coexist after THA.